Mr. Malcolm's list - Allain, Suzanne (Jove, 2020)
"Move over, Mr. Darcy, there's a new man in town . . . . It is a truth universally acknowledged that an arrogant bachelor insistent on a wife who meets the strictest of requirements--deserves his comeuppance. The Honorable Mr. Jeremy Malcolm is searching for a wife, but not just any wife. He's determined to elude the fortune hunters and find a near-perfect woman, one who will meet the qualifications of his well-crafted list. But after years of searching, he's beginning to despair of ever finding this paragon. And then Selina Dalton arrives in town . . . . Selina, a vicar's daughter of limited means and a stranger to high society, is thrilled when her friend Julia invites her to London. Until she learns it's part of a plot to exact revenge on Mr. Malcolm. Selina is reluctant to participate in Julia's scheme, especially after meeting the irresistible Mr. Malcolm, who seems very different from the arrogant scoundrel of Julia's description. But when Mr. Malcolm begins judging Selina against his unattainable standards, Selina decides that she has some qualifications of her own. And if he is to meet them he must reveal the real man behind . . . Mr. Malcolm's List."--